EFEKTIVITAS POSTER MAJALAH DINDING DALAM MENINGKATKAN MINAT BELAJAR GAYA DAN GERAK - Siregar, Hanif Luthfi; Simanihuruk, Lidia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2024)
This research aims to implement the wall magazine poster-based method on science learning interest on the theme of force and motion in class IV SD Negeri 060866 Medan Krakatau. The research method used was qualitative with a descriptive approach. Data were collected through observations, interviews and student evaluations. The results showed that students' understanding had a positive effect on science learning outcomes, where 90% of students showed interest in the poster media used. In addition, students' positive learning interest contributed to good learning outcomes. This study concludes that the use of poster media can increase students' interest and understanding in learning science, so it is expected to be applied more widely in the learning process.